Risk factor analysis for neonatal lamb mortality in Malpura sheep - SWARNKAR, C P; GOWANE, G R; PRINCE, L L L; SONAWANE, G G (The Indian Journal of Animal Sciences, 2019)
The magnitude of risk for neonatal mortality (NM) due to non-genetic factors was assessed using data on 5,722 Malpura lambs born during 1991–2016 at ICAR-Central Sheep and Wool Research Institute, Avikanagar, Rajasthan. The association of non-genetic factors influencing lamb mortality was obtained by odds ratio (OR). The overall annual NM was 4.07% with around 3 times higher in hebdomadal (3.15%) than post-hebdomadal (0.93%) phase. In comparison to lambs with >3.50 kg birth weight, the OR varied from 2.03 (birth weight 3.01–3.50 kg) to 19.29 (birth weight <2.00 kg). Neonatal mortality was significantly higher (6.51%) in lambs born to younger ewes (up to 2 yr). The parity of dam had significant effect on NM with maximum mortality in lambs born to ewes in 1st (5.59%) parity. Dam’s weight at lambing revealed significantly maximum (32.35%) mortality in lambs born to ewes with <20.0 kg body weight. In comparison to ewes with 30–35 kg body weight at lambing, the OR for NM was maximum (17.28) in lambs born to ewes with <20.0 kg body weight at lambing. The causes of neonatal lamb mortality exhibited predominance of septicaemia/ toxaemia with 25.75% contribution in total deaths followed by neonatal inanition (21.89%), pneumonia (12.02) and enteritis (8.58%). The study revealed that NM during early phase of life was primarily influenced by both lamb and ewe factors. Strategies should be adopted for proper nutritional care of primiparous and weak ewes during gestation, intensive monitoring of lamb and ewes during the neonatal period with ensured colostrum or milk replacer feeding and suitable housing facility to minimize the neonatal losses.